PROTECTION OF THE RIGHT TO IMPLEMENT PATENTS IN THE TECHNOLOGY AND INVESTMENTS IN INDONESIA - Atsar, Abdul (TANJUNGPURA LAW JOURNAL, 2019)
Abstract Today, businesses in industry and technology are faced with increasingly keen competition challenges. Business in industry and technology can be done by way of technology transfer, which is expected to increase on the absorption of investment and the provision of employment. For that very necessary regulation that can support the investment climate and technology transfer such as Patent law. Not only oriented inward with the spirit of nationalism but also must globalize or in accordance with international regulations in order to avoid clash with other countries. The purpose of this study is to examine the protection of patent application rights in Technology Transfer and Investment Absorption in Indonesia. This research method is normative juridical. This approach is the legal, conceptual and historical approach. This research includes descriptive research, Data used in this research is primary data and secondary data source. Data analysis techniques, which use is qualitative normative descriptive analysis. The results of this study can be seen that there are several Articles in the Law No.13 Year 2016 on Patents that have a high spirit of nationalism that is expected to improve technological progress and increase investment in Indonesia but it is contrary to international law or agreement TRIPs, among them is Article 20, Article 4, Article 78 and Article 120. The Articles are contradictory to Article 27 TRIPs, it is necessary to amend the rules of Patent through the Act and the implementing regulations under it and to make qualification and classification of the products are required to make or use the process in Indonesia so as to appeal to domestic and foreign investors from abroad to invest their capital and bring patent technology to Indonesia.  AbstrakSaat ini, bisnis di industri dan teknologi dihadapkan pada tantangan persaingan yang semakin tajam. Bisnis dalam industri dan teknologi dapat dilakukan dengan cara transfer teknologi, yang diharapkan dapat meningkatkan penyerapan investasi dan penyediaan lapangan kerja. Untuk itu sangat diperlukan regulasi yang dapat mendukung iklim investasi dan alih teknologi seperti hukum paten. Tidak hanya berorientasi ke dalam dengan semangat nasionalisme tetapi juga harus mengglobal atau sesuai dengan peraturan internasional untuk menghindari bentrokan dengan negara lain. Tujuan dari penelitian ini adalah untuk menguji perlindungan hak paten dalam transfer teknologi dan penyerapan investasi di Indonesia. Metode penelitian ini adalah yuridis normatif. Pendekatan ini adalah pendekatan hukum, konseptual, dan historis. Penelitian ini termasuk penelitian deskriptif, data yang digunakan dalam penelitian ini adalah data primer dan sumber data sekunder. Teknik analisis data, yang digunakan adalah analisis deskriptif normatif kualitatif. Hasil penelitian ini dapat dilihat bahwa ada beberapa Pasal dalam UU No.13 Tahun 2016 tentang Paten yang memiliki semangat nasionalisme tinggi yang diharapkan dapat meningkatkan kemajuan teknologi dan meningkatkan investasi di Indonesia tetapi bertentangan dengan hukum internasional atau perjanjian TRIPs, di antaranya adalah Pasal 20, Pasal 4, Pasal 78 dan Pasal 120. Pasa-pasal tersebut bertentangan dengan Pasal 27 TRIPs, perlu untuk mengubah aturan paten melalui Undang-Undang dan peraturan pelaksanaan di bawahnya dan untuk membuat kualifikasi dan klasifikasi produk diperlukan untuk membuat atau menggunakan proses di Indonesia untuk menarik investor domestik dan asing dari luar negeri untuk menginvestasikan modalnya dan membawa teknologi paten ke Indonesia.